A content analysis of the aims, strategies, and effects of food and nonalcoholic drink advertising based on advertising industry case studies - Kiran Nanchahal; Milica Vasiljevic; Mark Petticrew (Wiley, 2022)
Abstract Background Placing limitations on advertising of food and nonalcoholic drinks to children is an effective strategy in addressing childhood obesity. The industry maintains that further restrictions are unnecessary. Aims To ascertain whether the advertising campaigns were successful according to the industry evaluations and more specifically the effects of marketing on children. Materials & Methods A total of 117 case studies (1980-2016) published by the advertising industry which evaluate the effects of advertising campaigns were reviewed. This industry data source had been previously used to analyze the effects of alcohol advertising campaigns. The nutrition profile of the products was assessed by applying the World Health Organisation Nutrition Profile model designed to restrict the marketing of foods and beverages to children. Results The food and drink industry advertising campaigns target specific consumers including children, use several persuasive marketing techniques (utilizing celebrities and gamification), often position unhealthy products as healthy, and lead to increased sales of the advertised product with good returns on investment. The health‐related claims made, and aspects of the campaigns related to the marketing of the products to children are summarized. Discussion Our analysis of food and non‐alcoholic drinks case studies aligns with similar analyses of tobacco and alcohol advertising Conclusion This analysis, based on internal industry data, presents important evidence on the effects of advertising on consumption‐related outcomes and the mechanisms by which they are achieved.